Energy Recovery Potential of Livestock Waste with Thermal and Biological Technologies: Analysis on Cattle, Sheep, Goat and Chicken Manure - Altan, Hasan Suphi; Orhon, Derin; Sozen, Seval (International Journal of Energy Economics and Policy, 2022)
This study aims to establish the scientific link between the livestock wastes and energy recovery processes to implement the most appropriate technology at the highest economic benefit. The evaluation was based on the recovery of the potential energy of the mixture of four livestock wastes (cattle, sheep, goat, egg chicken) by four different energy recovery processes. Incineration, gasification, pyrolysis at 550°C and 750°C were applied as thermal processes together with the anaerobic digestion as biochemical process. The recovery performance of each process was evaluated within a defined design algorithm considering all significant parameters in seven geographical regions and in Turkey as a whole. Incineration seems to be the most efficient energy recovery process with 0.43 MWe/t for Turkey. Gasification took the second place in the energy recovery ranking with 0.34 MWe/t, 21% less than incineration. Pyrolysis expressed an energy recovery rate of 0.15 MWe/t at 550°C and a twice higher rate at 750°C, at a level close to gasification. Anaerobic digestion exerted a recovery potential of 0.21 MWe/t for the livestock waste considered. Energy recovery from livestock waste not only contributes to energy production, but also provides compliance with the concept of reducing emissions and sustainable environment.